Books Reviews and Review Essay. Issue 2 (1st September 2020) - Unknown
Abstract : Tony Bayfield, Being Jewish Today: Confronting the Real Issues, Bloomsbury Continuum, 2019, £18.99 Marika Henriques, The Hidden Girl: The Journey of a Soul, Shepheard-Walwyn Publishers Ltd., 2018, £25.00 Marc Saperstein, Agony in the Pulpit: Jewish Preaching in Response to Nazi Persecution and Mass Murder 1933–1945, Hebrew Union College Press, 2018, $95.00